Kemajuan Teknologi Rekayasa Genetika Ditinjau dari Filsafat Evolusi Darwin - Geterudis Kerans (Jurnal Filsafat Indonesia, 2022)
Evolution occurs because of the process of changing species within a certain period of time with the aim of being able to adapt to their environment and these changes will be passed on to the next generation or to their descendants. The theory of evolution in the Biological Sciences came to light with the publication of Charles Darwin's book (On the Origin of Species by Means of Natural Selection) in 1859, which presented cases of evolution and was able to relate previously confusing collections of facts. In the 1930s scientists combined Darwin's natural selection with Mendelian's theory of heredity and formed the modern evolutionary synthesis "Neo-Darwinism". Neo Darwinism theory states that evolution is based on gene mutations that work together at the protein network level and change the phenotype of living things. Current technological developments allow scientists to carry out genetic engineering and genetic engineering processes based on Darwin's theory of evolution. The purpose of this paper is to conduct a philosophi study (Epistemology, Ontology and axiology) of Darwin's Evolution in technological progress. This article was prepared using a library research and review approach. The study of genetic engineering epistemology explains how genetic engineering techniques were obtained and how genetic engineering techniques developed. Ontology studies talk about the nature of genetic engineering and the scientific structure of genetic engineering. While the study of Axiologydiscusses the benefits and disadvantages caused by genetic engineering.